Controllable synthesis of core-sheath structured aligned carbon nanotube/titanium dioxide hybrid fibers by atomic layer deposition. (October 2017) - Li, Mingyang; Zu, Mei; Yu, Jinshan; Cheng, Haifeng; Li, Qingwen; Li, Bing
Abstract: Carbon nanotube (CNT)-inorganic hybrids have been extensively investigated due to their potential to become the next-generation materials for applications in energy and environment. However, the random dispersion of CNTs and the low-quality inorganic phases may hinder their use in flexible and multi-functional devices. Herein, we synthesize the multi-functional aligned CNT/titanium dioxide (TiO2 ) hybrid fibers involving CNT-based continuous fibers coated by TiO2 through the atomic layer deposition (ALD). The aligned CNT/TiO2 hybrid fibers with various thicknesses of TiO2 layer can be simply obtained by changing the ALD cycles. Microscopic analysis of the surface morphologies and structures of the as-prepared hybrid fibers confirms the conformal oxide coating on the CNT fibers. Furthermore, the tensile strength of the hybrid fiber varies little after the deposition of TiO2 while its electrical conductivity decreases by 28.3% when the ALD cycle number is increased to 715 cycles. Due to its unique self-limiting characteristic, ALD has precise control in deposition at the atomic level and can facilitate the conformal and uniform coating of TiO2 on the CNT fibers while preserving the alignment of CNT bundles within the fiber, which may offer a promising solution for fabricating the novel multi-functional fibers. Graphical abstract: